MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK MELALUI MODEL DISCOVERY LEARNING - MIFTAHUL JAN'NAH (Jurnal Edukasi dan Penelitian Matematika, 2021)
Various of studies indicate that mathematics learning achievement of Indonesian students is classified as low. The main factors causing this issue are passive teaching-learning process that related to the low  understanding of student’s mathematical problem solving. The purpose of this article is written to examine the influence of model discovery learning of student’s mathematical problem solving. The methods of data collection used in this article are to search and review the relevant journals after that process the data. The result of this study is indicate that student’s understanding of mathematical problem solving increase also students learning process become more active by using a model discovery learning.Keywords__mathematical problem solving abilities, Discovery Learning